The Use of the Pipeline Embolization Device in the Management of Recurrent Previously Coiled Cerebral Aneurysms. Issue 5 (15th July 2015) - Daou, Badih; Starke, Robert M.; Chalouhi, Nohra; Tjoumakaris, Stavropoula; Khoury, Jean; Hasan, David; Rosenwasser, Robert H.; Jabbour, Pascal M.
Abstract: BACKGROUND: The biggest downside of cerebral aneurysm coiling is the high rates of recurrence and retreatments. With the increasing number of aneurysm recurrences after failed coiling procedures, the best retreatment strategy remains unknown. OBJECTIVE: To assess the efficacy and safety of the Pipeline Embolization Device (PED) in the treatment of recurrent previously coiled aneurysms. METHODS: Thirty-three patients who underwent treatment with the PED of a recurrent previously coiled aneurysm were retrospectively identified. Efficacy was assessed in terms of angiographic occlusion at the latest cerebral angiogram, recurrence and retreatment rates after PED placement, and clinical outcome at the latest follow-up. Safety was assessed by looking at the complications, morbidity, and mortality after PED treatment. RESULTS: The mean patient age was 53 years. The mean percent recurrence from coiling to PED placement was 34%. The mean time from coiling to PED placement was 40 months. PED treatment resulted in complete aneurysm occlusion in 76.7% of patients and near-complete aneurysm occlusion (≥90%) in 10%, for a total rate of complete and near-complete aneurysm occlusion of 86.7%. All patients, including those with incomplete aneurysm occlusion, had a significant reduction in aneurysm size. Two aneurysms required another retreatment after PED placement (6.2%). Ninety-seven percent of patients had a good clinical outcome. Complications were observed in 1 patient (3%), who suffered an intracerebral hemorrhage. There were no mortalities. CONCLUSION: The use of the PED in the management of recurrent, previously coiled aneurysms is safe and effective in achieving aneurysm occlusion.